Supernatural Aspect In The Conjuring 3 The Devil Made Me Do It Movie Script - Herlina, Herlina; Moelier, Dahlia D.; Rijal, Tabhan Syamsu (Humaniora: Journal of Linguistics, Literature, and Education, 2023)
This data aimed to identify the supernatural aspect and to found out the impacts of the main character to the society in The Conjuring 3 The Devil Made Me do It movie script. In analyzing the data, the researcher applied descriptive qualitative method to explain the types of supernatural aspects and the impacts of the main character to the society in The Conjuring 3 The Devil Made Me do It movie script. This research based on Dunwich theory about Supernatural Aspect. The researcher found that there were four types of supernatural aspects in The Conjuring 3 The Devil Made Me do It movie script: True Tales of Ghost and Hunting, The Necromantic Arts, Possession, Obsession, Exorcism, Spells and Sorcery. The writer also found the impact of the main character to the society which was the main character could change the perspective of other characters from negative to positive. The researcher had found 5 data of impacts